2015
DOI: 10.1039/c5cc01548k
|View full text |Cite
|
Sign up to set email alerts
|

Achieving room temperature DNA amplification by dialling in destabilization

Abstract: The ability to amplify nucleic acid biomarkers at room temperature has remained elusive despite the great need of diagnostics suitable for the point of care. To exponentially amplify DNA within a wide range of ambient temperatures (18-26 °C), we explore combining two destabilizing elements in our isothermal lesion-induced DNA amplification system. We demonstrate rapid DNA amplification at the bench without a heat source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…A wide range of operational temperatures may also allow this method to be applicable at room temperature, circumventing the need for heating equipment, a goal which is desirable for point-of-care assays. [30][31][32] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 To accomplish this goal, at both ends of each linker strand we introduced differing lengths of overhangs, i.e. nucleotide extensions that would not participate in hybridization with the DNA-AuNP probes.…”
Section: Resultsmentioning
confidence: 97%
“…A wide range of operational temperatures may also allow this method to be applicable at room temperature, circumventing the need for heating equipment, a goal which is desirable for point-of-care assays. [30][31][32] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 To accomplish this goal, at both ends of each linker strand we introduced differing lengths of overhangs, i.e. nucleotide extensions that would not participate in hybridization with the DNA-AuNP probes.…”
Section: Resultsmentioning
confidence: 97%
“…As mentioned, our previous work showed that the replication temperature in LIDA can be tuned by the introduction of a mismatch to the system, which is less destabilizing than an abasic group. [33] Thus, a T base was switched into a C base in one of the probes (DNA-Ia), which resulted in an A:C mismatch (square, Figure 1). This combination of destabilizing elements allowed us to lower the temperature from 37 °C to 28 °C (Figure S2B).…”
Section: Design Of Isothermal Rna-triggered Lidamentioning
confidence: 99%
“…Previously we reported the development of lesion-induced DNA amplification (LIDA), which was capable of rapid, exponential amplification of different 18 nucleotide DNA target sequences by incorporating a destabilizing abasic lesion into one of the target-complementary primers, or probes, in a ligase chain reaction. [33][34][35] With this approach, as little as 140 fM (2.1 attomoles) of target DNA was detected following a two-step serial amplification procedure. [35] In more recent work, it was revealed that adding a second destabilizing lesion consisting of a mismatch or another abasic group allowed the replication temperature to be tuned from 18 -30 °C for a particular target sequence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Product inhibition implies that a newly formed complementary template is very unlikely to dehybridize from the template. However, Gibbs-Davis and her team 1 have developed a method to circumvent product inhibition based on mismatches and lesions between the complementary templates that destabilize them and thus enables a continued replication process. In this work we explore in simulation the thermodynamic and kinetic properties of lesion induced DNA amplification processes.…”
Section: Introductionmentioning
confidence: 99%